Evaluation performance characteristics for geometric modeller - Chong, Heng Fatt. (2008)
The purpose of this thesis is to explore for alternative ways to evaluate solid modelers whose domain of representation is Boundary-representation (B-rep). In the analysis, Unigraphics is selected as the solid modeler. The Euler Law was used to break down the basic operations through its various Euler operators. Analysis carried out in this manner provides an in-depth understanding of development of the structure and algorithm of the B-rep solid modeler.